Lifeworld as "unit of analysis". Issue 4 (3rd April 2018) - Gorichanaz, Tim; Latham, Kiersten F.; Wood, Elizabeth
Abstract : Purpose: The authors discuss the lifeworld as a research concept for the field of information behaviour, which serves to problematise the concept of unit of analysis. In so doing, the authors demonstrate how the lifeworld can be adopted as a unit of analysis in information behaviour research, that is, how research can be based in the lifeworld rather than merely looking at the lifeworld. The paper aims to discuss these issues. Design/methodology/approach: The authors first situate our discussion in the current of information behaviour scholarship. The authors then introduce the concepts of lifeworld and unit of analysis and consider how they intersect. Next, to show the importance of the lifeworld, the authors present two recent studies in which the lifeworld emerged. Finally, the authors discuss how lifeworld-based research can be conducted more conscientiously. Findings: Though many research approaches deal with lived experience in one way or another, they tend not to fully grasp these experiences. As opposed to units of analysis such as individual, social group, person-in-situation, etc., using lifeworld as a unit of analysis allows phenomena to be researched holistically and without reductionism. Research limitations/implications: The authors limit the discussion to the concept of the lifeworld as developed by Husserl, the concept's originator. The lifeworld has been discussed and extended by other authors since, but this work is not considered here. The viewpoint is offered as a supplementary perspective, meant to be enriching to our field of study, rather than divisive. Originality/value: This is the first time the concept of the lifeworld has been fully explicated in information science. As the authors discuss, two recent information behaviour studies that "discovered" the lifeworld through their analysis. Future studies that attend to the lifeworld from the start have the capacity to build on this work and extend the horizons of information science.